Microneedling for the Treatment of Scars: An Update for Clinicians - Juhasz MLW; Cohen JL (Dove Medical Press, 2020)
Margit LW Juhasz,1 Joel L Cohen1,2 1University of California, Department of Dermatology, Irvine, CA, USA; 2AboutSkin Dermatology and DermSurgery, Greenwood Village, CO, USACorrespondence: Margit LW JuhaszUniversity of California, Department of Dermatology, 118 Med Surge I, Irvine, CA 92697, USATel +1 718-309-7368Email mjuhasz@uci.eduBackground: Microneedling (MN) is used for the treatment of scars, amongst other indications. Although used in Asia and the Middle East for decades, related to the supposed lack of post-procedure pigmentary alterations even in darker skin types, MN only recently gained attention in the United States as an effective, well-tolerated aesthetic treatment.Materials and Methods: A systematic review of the Medline database was completed using search terms “microneedle” or “microneedling” or “micro needle” or “micro needling” and “scar”. Included articles were written in English and discussed the use of MN for the treatment of scars in human subjects.Results: Fifty-eight studies were included for review, with a total of 1845 patients treated for acne scarring, hypertrophic or keloid scars, and those resulting from surgery, trauma, varicella or smallpox. MN and its counterpart fractional radiofrequency MN (FRF-MN) were used as monotherapy or in combination with topical, surgical or systemic modalities. MN and FRF-MN treatment resulted in clinical improvement of scar appearance from baseline. No serious adverse events occurred.Conclusion: MN is a well-tolerated, minimally invasive procedure that can be used for the treatment of scars with a high level of patient satisfaction. Further clinical studies are needed to develop standardized treatment protocols.Keywords: microneedling, laser, peel, platelet-rich plasma, scar